Performance of Prototypes for the Barrel Part of the ANDA Electromagnetic Calorimeter. (August 2016) - Rosenbaum, Christoph; Diehl, S.; Dormenev, V.; Drexler, P.; Kavatsyuk, M.; Kuske, T.; Nazarenko, S.; Novotny, R.; Rosier, P.; Ryazantsev, A.; Wieczorek, P.; Wilms, A.; et al.
Abstract: The performance of the most recent prototypes of the ANDA barrel electromagnetic calorimeter (EMC) will be compared. The first large scale prototype PROTO60 was designed to test the performance of the improved tapered lead tungstate crystals (PWO-II). The PROTO60 which consists of 6 × 10 crystals was tested at various accelerator facilities over the complete envisaged energy range fulfilling the requirements of the TDR of the ANDA EMC in terms of energy, position and time resolution. To realize the final barrel geometry and to test the final front end electronics, a second prototype PROTO120 has been constructed. It represents a larger section of a barrel slice, containing the most tapered crystals and the close to final components for the ANDA EMC. The performance of both prototypes will be compared with a focus on the analysis procedure including the signal extraction, noise rejection, calibration and the energy resolution. In addition, the influence of the non-uniformity of the crystal on the energy resolution will be discussed.